The influence of E-auditing adoption on internal audit department performance amid COVID-19 in Saudi Arabia - Abdulwahab Mujalli (Cogent Business & Management, 2024)
Over the last decade, rapid advances in information systems (ISs) have greatly reshaped and changed the nature of doing business and how its performance is measured, with Electronic Auditing (E-auditing) emerging as a pivotal element in improving organizational efficiency. This study addresses the challenges faced in manually implementing audits and underscores the necessity for transitioning to electronic audit systems. The manual approach has limitations regarding the accuracy of operations, so to enhance performance, E-auditing is now imperative. The purpose of the study is to evaluate E-auditing in the public sector of Saudi Arabia, utilizing DeLone and McLean's information system model (DM ISM). The focus is on vital factors including information quality, system quality, service quality, system usage and user satisfaction and their influence on the performance of internal audit departments, particularly during the challenges posed by the recent COVID-19 pandemic. This research employs a quantitative approach, utilizing a self-administered survey questionnaire to collect data from E-auditing users in the Saudi public sector. The study applies partial least squares structural equation modelling (PLS-SEM) to validate the gathered data. Findings reveal that information quality and system quality significantly influence E-auditing usage. While service quality exhibits no marked effect on usage, the study establishes a strong relationship between E-auditing usage and user satisfaction. Effective E-auditing usage and satisfied users contribute convincingly to the improved performance of internal audit departments. The paper concludes with implications, limitations, and suggestions for future studies.
Keywords: 650; Electronic auditing; e-auditing usage; user satisfaction; Covid-19; Saudi Arabia